1987
DOI: 10.1007/bf00296252
|View full text |Cite
|
Sign up to set email alerts
|

Effect of verapamil on daunorubicin accumulation in Ehrlich ascites tumor cells

Abstract: Previous studies have demonstrated that verapamil may overcome resistance to anthracyclines. In vitro and in vivo experiments were performed on wild-type and resistant Ehrlich ascites tumor cells. Verapamil in concentrations of 25-50 microM enhances the accumulation of daunorubicin (DNR) in resistant cells to the same level as in wild-type cells. No significant effect of verapamil on influx or nuclear binding could be demonstrated, indicating that verapamil enhances DNR uptake by blocking active drug extrusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

1988
1988
1994
1994

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 9 publications
0
13
0
1
Order By: Relevance
“…This is in spite of that VER at 25 ILM has been shown to increase intracellular DNR in EHR2/ DNR + to levels approaching those found in sensitive EHR2 cells (Friche et al, 1987), and also that Tween 80 at 0.001% v/v significantly enhanced DNR accumulation in EHR2/ DNR + (T. Skovsgaard, unpublished results). This is in agreement with our previous results (Sehested et al, 1989) which failed to demonstrate any specific DNR binding site on the EHR2/DNR + plasma membrane.…”
Section: Modulation Of Vcr Induced Cell Cycle Perturbationsmentioning
confidence: 95%
“…This is in spite of that VER at 25 ILM has been shown to increase intracellular DNR in EHR2/ DNR + to levels approaching those found in sensitive EHR2 cells (Friche et al, 1987), and also that Tween 80 at 0.001% v/v significantly enhanced DNR accumulation in EHR2/ DNR + (T. Skovsgaard, unpublished results). This is in agreement with our previous results (Sehested et al, 1989) which failed to demonstrate any specific DNR binding site on the EHR2/DNR + plasma membrane.…”
Section: Modulation Of Vcr Induced Cell Cycle Perturbationsmentioning
confidence: 95%
“…Resistance to DNR was developed and maintained in vivo in mice as previously described in detail (Dan0, 1971). In vivo the subline is at least 16-fold resistant to DNR (Friche et al, 1987) and in vitro in a clonogenic assay about 80-fold resistant (Friche et al, 1990b). No (Merck, Germany) with the solvent system ethyl acetate/diethyl ether (2:1, v/v, Rf 0.12), and extracted from the silica by ethanol (2 x 1 ml).…”
mentioning
confidence: 99%
“…Moreover, neither the calcium ionophore A23187, the calcium chelator EGTA, nor the inorganic inhibitor of calcium influx lanthanum modify perhexilineincreases of daunorubicin cytotoxicity (Ramu et al 1984a) and EGTA has been shown not to increase daunorubicinaccumulation or cytotoxicity in P388/ADR cells (Ramu er al. 1984a;Friche et al 1987). Thus CCBs do not appear to enhance anthracycline cytotoxicity through a modification of cellular calcium fluxes.…”
Section: Mechanism Of Interactionmentioning
confidence: 96%
“…Moreover, verapamil enhances adriamycin and daunorubicin activity against Ehrlich ascites carcinoma cells resistant to them in a dose-dependent way, significantly increasing the life span of the experimental animals bearing these cells. However, verapamil does not increase the cytotoxicity of these anthracyclines in Ehrlich ascites cells sensitive to them (Slater et al 1982;Friche et al 1987).…”
Section: Studies In Experimental Animal Tumour Cellsmentioning
confidence: 99%
See 1 more Smart Citation